PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR SISWA - Ando Hutagalung; Usler Simarmata (INPAFI (Inovasi Pembelajaran Fisika), 2015)
The purpose of this study was to determine the effect of cooperative learning model type Group Investigation (GI) on learning outcomes of students in the subject matter of temperature and heat in SMP PGRI 4 Medan. This type of research is quasi-experimental. The population of this entire class VIII SMP PGRI 4 Medan much as three classes. The sample in this study was taken as a random sampling of two classes. The instrument used  to determine student learning outcomes in the material temperature and heat in the form of multiple-choice questions numbered 20 and the observation sheet. The results obtained by testing hypotheses that there is a significant relationship between the use of cooperative learning model GI on student learning outcomes. Keywords: Cooperative learning model group investigation, learning outcomes.